Pengaruh Kompetensi, Independensi, Dan Profesionalisme Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi (Studi Empiris pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Setiawan, Nanang; , Drs. Wahyono, Ak. MA (2016)
The objectives of this research to empirically analyze the influence of competency, independency, and professionalism on audit quality, and to the influence of competency, independency, and professionalism to audit quality is moderated by auditor ethics, especially in the auditor working in KAP Surakarta and Yogyakarta.The population in this research are all auditors who worked on the KAP in Surakarta and Yogyakarta. Sampling was conducted using a purposive sampling method and number of samples of 70 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analyze Multiple Regression Analyze and Moderate Regression Analyze (MRA). The results showed that the effect on the competence and independence of audit quality, while professionalism had no effect on audit quality. Interaction competence and ethics of auditors, ethics and auditor independence interaction effect on audit quality, while the interaction of professionalism and ethical auditor has no effect on audit quality. The coefficient of determination shows that jointly competence, independence, professionalism and ethics of auditors contributed to the dependent variable (quality audit) is 38,4% while the remaining 61,6% is influenced by other factors outside of observation.